Biogeochemical feedbacks to ocean acidification in a cohesive photosynthetic sediment - Kay Vopel (Nature Portfolio, 2021)
Abstract Ecosystem feedbacks in response to ocean acidification can amplify or diminish diel pH oscillations in productive coastal waters. Benthic microalgae generate such oscillations in sediment porewater and here we ask how CO2 enrichment (acidification) of the overlying seawater alters these in the absence and presence of biogenic calcite. We placed a 1-mm layer of ground oyster shells, mimicking the arrival of dead calcifying biota (+Calcite), or sand (Control) onto intact silt sediment cores, and then gradually increased the pCO2 in the seawater above half of +Calcite and Control cores from 472 to 1216 μatm (pH 8.0 to 7.6, CO2:HCO3 − from 4.8 to 9.6 × 10−4). Porewater [O2] and [H+] microprofiles measured 16 d later showed that this enrichment had decreased the O2 penetration depth (O2-pd) in +Calcite and Control, indicating a metabolic response. In CO2-enriched seawater: (1) sediment biogeochemical processes respectively added and removed more H+ to and from the sediment porewater in darkness and light, than in ambient seawater increasing the amplitude of the diel porewater [H+] oscillations, and (2) in darkness, calcite dissolution in +Calcite sediment decreased the porewater [H+] below that in overlying seawater, reversing the sediment–seawater H+ flux and decreasing the amplitude of diel [H+] oscillations. This dissolution did not, however, counter the negative effect of CO2 enrichment on O2-pd. We now hypothesise that feedback to CO2 enrichment—an increase in the microbial reoxidation of reduced solutes with O2—decreased the sediment O2-pd and contributed to the enhanced porewater acidification.